Pengaruh Solvabiltas dan Profitabilitas Terhadap Harga Saham Perusahaan Jasa Sub Sektor Kontruksi Bangunan yang terdaftar di Bursa Efek Indonesia Periode 2012-2017 - Ellena Ratna Pujiarti; Ima Kristina Yulita (Fakultas Ekonomi, Universitas Sanata Dharma Yogyakarta, 2020)
The purpose of this research is to find out the influence of solvability and profitability on the stock price of building construction. The sample of this research includes six companies listed in BEI in the period from 2012 to 2017. This sampling method used in this research is purposive sampling. The data consists of secondary data collected using the documentation method. The result shows that partially solvability and profitability had significant influence on the stock prices.